Publisher Correction: The evaluation of monoclonal gammopathy of renal significance: a consensus report of the International Kidney and Monoclonal Gammopathy Research Group - Leung, Nelson; Bridoux, Frank; Batuman, Vecihi; Chaidos, Aristeidis; Cockwell, Paul; D'Agati, Vivette D; Dispenzieri, Angela; Fervenza, Fernando C; Fermand, Jean- Paul; Gibbs, Simon; Gillmore, Julian D; Herrera, Guillermo A; et al. (Nature reviews. Nephrology, 2019)
In the key to Figure 1 of this article, 'Amyloid microtubules' has been corrected to 'Microtubules'.